Adaptation of the Wawel Royal Castle to the Needs of People with Mobility Impairments - Jeżowski, Rafał (Protection of Cultural Heritage, 2022)
Wawel Royal Castle is visited by about one and a half million people every year. Wawel Hill is virtually accessible to people with disabilities. The castle's interiors, accessible to visitors via two staircases on the side of the Arcade Courtyard, were not accessible to wheelchair users. During the works carried out in 2017-2019 as part of the EU project "Wawel Castle – Heritage for the Future", numerous architectural barriers in the form of thresholds, single steps in front of the entrances on the cloisters and others were eliminated in the building, and an elevator was built in place of the staircase dating back to the time of General Governor Hans Frank. The article describes in detail the construction work carried out inside the building and on the cloisters, as well as the construction of a modern crane, specially constructed for the Castle. Its detailed parameters are given. An attempt was made to evaluate the project using seven conservation principles as criteria for evaluation. The content is enriched by numerous unique photos taken before and during the works and today inside the shaft, inaccessible to the eyes of users. The text brings the reader closer to the work of constructing a crane in a historic building in accordance with conservation principles in an accessible way, and can be useful for training conservationists as a case study.